ANALISIS PENGUKURAN KINERJA KEUANGAN PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR INDEKS LQ45 DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2020 - Lincolen, Yogi; Novika; Shinta Lestari, Deara (Jurnal Akuntansi Bisnis Dan Keuangan, 2021)
Ratings for the company’s financial performance is an important thing to do, it is used to measure and evaluate, in order to get an overall picture of the financial position. The method used to measure the financial performance that is one method of analysis of financial statements. Financial statement analysis methods involve some ratio, ie the ratio of liquidity, solvency, and profitability. The purpose of this study to determine the financial performance of PT Indofood CBP Sukses Makmur Tbk and PT Indofood Sukses Makmur Tbk period 2016-2020 by using the ratio of liquidity, solvency, profitability. Discussion of the results obtained that the financial performance of of PT Indofood CBP Sukses Makmur Tbk and PT Indofood Sukses Makmur Tbk annually seemingly with ratios fluctuate, this is due to an increase or decrease in financial statement items, for example on sales, inventory, profit, and others.